Recent Developments in the Study of Recrystallization - Wilson, Peter (IntechOpen, 2013)
Recrystallization is a phenomenon moderately well documented in the geological and metallurgical literature. This book provides a timely overview of the latest research and methods in a variety of fields where recrystallization is studied and is an important factor. The main advantage of a new look at these fields is the rapid increase in modern techniques, such as TEM, spectrometers and modeling capabilities, all of which are providing us with far better images and analysis than ever previously possible. This book will be invaluable to a wide range of research scientists; metallurgists looking to improve properties of alloys, those interested in how the latest equipment may be used to image grains and to all those who work with frozen aqueous solutions where recrystallization may be a problem.